Main Edges of Mavjuda Hamidova's Literature Activity - Hayitov, Shavkat (FILOLOGIYA UFQLARI JURNALI, 2024)
Abstract: The article discusses the textual activity of the talented scientist Mavjuda Hamidova. Factors such as scientific theoretical aspects of the problem of the style of the textual scholar, the period that created it, creative environment, talent, skills were considered on the example of the work of the literary scholar Mavjuda Hamidova. The services of the textual scholar Hafiz Khorezmi, poet of the XIV century, and Mirzo Kulfat, a poet from Tashkent, were studied from the point of view of textual studies and published. The scientific and critical text of Alisher Navoi's works "Saddiy Iskandariy", "Muhokamat ul-lug`atayn", "Mahbub ul-Qulub" was drawn up by Mavjuda Hamidova. In particular, on the basis of rare and rare sources, the scholar's skill in studying manuscript sources was revealed through the analysis and comparisons of the ways and methods of revealing the important ideas of the textualist's style by thoroughly analyzing the manuscripts.